O’zbekistonda soliq tushumlarini prognozlashtirish ishlarini samarali tashkil etish mexanizmini takomillashtirishning ahamiyati - Qurbanboyeva Odina Sayfiddin qizi, (SAMARALI TA’LIM VA BARQAROR INNOVATSIYALAR JURNALI, 2025)
In this article, the effective organization of tax revenue forecasting in the formation of the state budget, as a result of this, the prospects of socio-economic development of the state, the ways of effective organization of budget revenues are studied. Possibilities of fundamental improvement of the mechanism of formation and stabilization of budget revenues to the necessary level for the performance of state functions have been studied.